Characteristics and outcomes of adults with cytomegalovirus‐associated thrombocytopenia: a case series and literature review. (3rd August 2020) - Shragai, Tamir; Lebel, Eyal; Deshet, Dana; Varon, David; Avivi, Irit; Kirgner, Ilya; Sarid, Nadav
Summary: Cytomegalovirus (CMV) is a ubiquitous virus that infects people worldwide. CMV is known to trigger thrombocytopenia, but this association is probably underdiagnosed since CMV infection in healthy adults is usually either asymptomatic or causes only mild symptoms. A systematic literature review was carried out and yielded 23 publications that reported 25 patients. All haematology centres in Israel were searched for adult immunocompetent patients with CMV‐associated thrombocytopenia, and five new cases were identified. The median age of the combined 30 patients was 33 years (range 18–80), 73% were men, 77% presented with CMV‐related symptoms, 48% had enlarged spleens, 95% had atypical lymphocytes in peripheral blood and 68% had elevated transaminase levels. The response rate to first‐line steroid‐containing regimens was only 31%, whereas 11 patients who were treated with an anti‐CMV agent had a response rate of 82%. Moreover, four patients received thrombopoietin receptor agonists (TPO‐RA) to which three (75%) responded. Taken together, these distinctive features of a case with thrombocytopenia should alert to CMV infection as the source. While steroids were effective in less than one‐third of the cases, both anti‐CMV therapy and TPO‐RA exhibited excellent efficacy, suggesting that those agents should be introduced earlier in the therapeutic course.